Physiological traits suggest limited diapause response in false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae). (10th February 2014) - Terblanche, J. S.; de Jager, Z.; Boardman, L.; Addison, P.
Abstract The ability of a pest insect species to enter diapause, a physiological state of dormancy, has significant implications for population dynamics and pest management practises in agricultural landscapes. The false codling moth Thaumatotibia leucotreta is a major pest of deciduous and citrus fruit in southern Africa and a quarantine pest of international concern. Apart from an early field assessment that may have been compromised by taxonomic uncertainty surrounding cryptic developing life stages, no studies have investigated diapause induction within an experimental framework for this species, and none to date have used a suite of physiological traits potentially indicative of the diapause state. Here, we subjected larvae to cooling and shortening day length over a period of 14 days [Diapause Treatment (DT) group] relative to a similar‐aged control (CON) group held at optimal rearing conditions (25°C, 12 : 12 L : D) and tested if physiological traits, including resting metabolic rate, body freezing temperature (=supercooling point, equivalent to the low‐temperature mortality threshold) and body condition (body mass, body lipid and water content) varied in a direction that may be reflective of diapause induction. Mean metabolic rate in DT larvae was 0.044 ml CO2/h (mean mass: 52.7 mg), which was significantly higher than in CON larvae [0.025 ml CO2/h, mean mass: 51.5 mg (P = 0.04)]. Supercooling points were not statistically lower in the CON group than in DT larvae (DT:−15.6 ± 1.5°C; CON: −16.4 ± 2.8°C; P = 0.33). Measures of body size, body condition and resting water loss rates remained similar between groups. These results support the conclusion of early field observations that T. leucotreta does not undergo diapause that has significant implications for the management of the species.